2022
DOI: 10.3389/fmicb.2022.962124
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Phage Display: A promising selection strategy for the improvement of antibody targeting and drug delivery properties

Abstract: The discovery of hybridoma technology, described by Kohler and Milstein in 1975, and the resulting ability to generate monoclonal antibodies (mAbs) initiated a new era in antibody research and clinical development. However, limitations of the hybridoma technology as a routine antibody generation method in conjunction with high immunogenicity responses have led to the development of alternative approaches for the streamlined identification of most effective antibodies. Within this context, display selection tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 106 publications
0
17
0
Order By: Relevance
“…Further, the mAbs derived from animals also have a higher immunogenicity risk, a major hurdle in the development of therapeutic antibodies [ 6 ]. To overcome this hurdle, a human naïve or synthetic antibody library has been constructed to isolate target-specific human antibodies [ 43 , 44 , 45 ]. Although vaccination in humanized mouse models is also used as another reliable method for the generation of human mAbs, based on our previous work and similar reports by others, phage display-based antibody selection from an established antibody library can considered a faster and more efficient approach to isolating human recombinant mAbs than the antibody selection from the immune library [ 8 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, the mAbs derived from animals also have a higher immunogenicity risk, a major hurdle in the development of therapeutic antibodies [ 6 ]. To overcome this hurdle, a human naïve or synthetic antibody library has been constructed to isolate target-specific human antibodies [ 43 , 44 , 45 ]. Although vaccination in humanized mouse models is also used as another reliable method for the generation of human mAbs, based on our previous work and similar reports by others, phage display-based antibody selection from an established antibody library can considered a faster and more efficient approach to isolating human recombinant mAbs than the antibody selection from the immune library [ 8 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…This enables the reduction of the off-target tissue and protein interactions by eliminating non-specific ligands, enriching the recovery of specific ligands that specifically target the tumor. Despite its advantages, in vivo phage display selection remains relatively unexplored 44 , 45 . To date, few studies on cancer models have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…This powerful selection technique tends to simulate ideal living circumstances, improving the identification of specific ligands against challenging receptors in their native conformation [ 14 ]. In vivo screening offers advantages over conventional in vitro and in situ screening methods where the phage-displayed peptide candidates with desired features, including specificity, pharmacokinetics and stability can be selected in the complicated milieu of living animals [ 28 ]. Pasqualini and Ruoslahti were the first to demonstrate this technique in 1996, involving the identification of peptides homing to the vascular endothelium of renal and cerebral tissues in vivo [ 29 ].…”
Section: Biopanning: Selection Of Phage Displayed-based Peptidesmentioning
confidence: 99%
“…The phages are allowed to circulate for a few hours, promoting the binding of the displayed peptide to the specific targets that are expressed on the organ or tumour surface. Subsequently, the animals will be perfused and sacrificed to wash the unbound phages, followed by the collection of the interested organ to recover the bound phages [28]. Using this approach, various peptides such as CSSTRESAC [30], VAV3 [31], SP5-52 [32] and A54 [33] that target breast cancer cells, glioblastoma, lung tumour blood vessels and liver cancer cells, respectively, were identified in recent studies.…”
Section: Biopanning: Selection Of Phage Displayedbased Peptidesmentioning
confidence: 99%